A Bibliometric Analysis of Medication Compliance in Children with Asthma - Zhao J; Ding Y; Wang Z; Kou G; Xu S; Tai J; Zhang C; Guo Y; Yang J (Journal of Multidisciplinary Healthcare, 2025)
Jing Zhao,1 Yu Ding,1 Zhiyuan Wang,2 Guo Kou,1 Sen Xu,1 Jing Tai,1 Chunrui Zhang,1 Ying Guo,1 Jun Yang1 1Department of Pediatric Intensive Care, Nanyang Second People’s Hospital, Nanyang, Henan, 473012, People’s Republic of China; 2Department of Pediatric Intensive Care, The First Affiliated Hospital of Xinxiang Medical College, Xinxiang, Henan, 453100, People’s Republic of ChinaCorrespondence: Jun Yang, Department of Pediatric Intensive Care, Nanyang Second People’s Hospital, No. 66, Jianshe East Road, Wancheng District, Nanyang, Henan, 473012, People’s Republic of China, Tel +86 18503772257, Email yangj2024j@163.comObjective: Bibliometrics was used to visualize the literature data of the current study on medication compliance in children with asthma, which can provide reference for improving the medication compliance of children with asthma.Methods: Using the bibliometrix package in R4.4.1, all the research literatures related to the medication compliance of children with asthma in the WOS core database were used, and the data visualization analysis of the retrieved research literatures was carried out.Results: A total of 285 research literatures on medication compliance in children with asthma were screened out. The earliest related research was published in 2009, and reaching its peak in 2019. The number of publications and citations related to medication compliance in children with asthma in the United States ranked first. J Allergy Clin Immun has 1043 citations in related journals. The analysis of cumulative publication volume shows that from 2009 to 2024, Journal of Asthma has the largest cumulative publication volume. Halterman Js is the most authoritative. The most frequently used keyword in these articles is “asthma”. Statistical analysis of the high-frequency keywords in the literature on medication compliance in children with asthma showed that the top three high-frequency words were medication adherence, followed by unplanned children and childhood asthma.Conclusion: The study on medication compliance in children with asthma was first published in 2009, and the research heat increased year by year. The most authoritative author in the field of medication compliance in children with asthma is Halterman Js. Journal of Asthma magazine is interested in the research field of medication compliance in children with asthma.Keywords: children, asthma, medication adherence, bibliometrics